ChemInform Abstract: Direct Functionalization of Unactivated C—H Bonds Catalyzed by Group 3—5 Metal Alkyl Complexes. Issue 13 (1st April 2014) - Tsurugi, Hayato; Yamamoto, Koji; Nagae, Haruki; Kaneko, Hiroshi; Mashima, Kazushi
Abstract Review: 85 refs.